No change in running mechanics with live high -train low altitude training in elite distance runners - Stickford, A. S. L.; Wilhite, D. P.; Chapman, R. F. (International Journal of Sports Physiology and Performance, 2017)
Investigations into ventilatory, metabolic, and hematological changes with altitude training have been completed; however, there is a lack of research exploring potential gait-kinematic changes after altitude training, despite a common complaint of athletes being a lack of leg "turnover" on return from altitude training. Purpose: To determine if select kinematic variables changed in a group of elite distance runners after 4 wk of altitude training. Methods: Six elite male distance runners completed a 28-d altitude-training intervention in Flagstaff, AZ (2150 m), following a modified "live high-train low" model, wherein higherintensity runs were performed at lower altitudes (945-1150 m) and low-intensity sessions were completed at higher altitudes (1950-2850 m). Gait parameters were measured 2-9 d before departure to altitude and 1 to 2 d after returning to sea level at running speeds of 300-360 m/min. Results: No differences were found in ground-contact time, swing time, or stride length or frequency after altitude training (P > .05). Conclusions: Running mechanics are not affected by chronic altitude training in elite distance runners. The data suggest that either chronic training at altitude truly has no effect on running mechanics or completing the live high-train low model of altitude training, where higher-velocity workouts are completed at lower elevations, mitigates any negative mechanical adaptations that may be associated with chronic training at slower speeds.